Feasibility and acceptability of a peer provider delivered substance use screening and brief intervention program for youth in Kenya - Florence Jaguga; Edith Kamaru Kwobah; Ali Giusto; Edith Apondi; Julius Barasa; Mercy Korir; Wilter Rono; Gilliane Kosgei; Eve Puffer; Mary Ott (BMC, 2023)
Abstract Background Youth in sub-Saharan Africa are at high risk of substance use yet lack access to substance use interventions. The goal of this project was to evaluate the feasibility and acceptability of a peer-delivered, single-session substance use screening and brief intervention program for youth in Kenya. Methods This was a convergent parallel mixed methods study utilizing both quantitative and qualitative approaches. Two trained peer providers administered the screening and brief intervention program to 100 youth aged 15-24 years. To evaluate the implementation of the intervention, we collected quantitative and qualitative data. Feasibility and acceptability were quantitatively assessed using the Dissemination and Implementation Measures. Fidelity was assessed by rating all 100 audio-recorded sessions using a checklist. To obtain qualitative feedback on the intervention, we conducted five focus group discussions with 25 youths and six semi-structured interviews with two peer providers and four clinic leaders. The semi-structured interviews were guided by the Consolidated Framework for Implementation Research. Quantitative data was analyzed via descriptive statistics using STATA. Qualitative data was analyzed using thematic analysis with NVIVO. Results The lifetime prevalence of any substance use was 50%. The mean level of acceptability of the intervention from the perspective of the youth was 3.53 (SD 0.15), meaning that the youth found the intervention to be acceptable "a lot" of the time. Mean levels of implementation outcomes (acceptability, adoption, Acceptability, Appropriateness, Feasibility, Reach/access, Organizational climate, General leadership skills, and Sustainability) as rated by peer providers and clinic staff ranged between 2.61 ("a moderate amount") and 4.0 ("a lot"). In qualitative data, youth reported that the intervention was helpful and useful in enabling them to stop or reduce substance use. The peer providers felt that the intervention was easy to implement, while the clinic leaders felt that available resources were adequate, and that the intervention aligned well with the goals of the clinic. Conclusion Our findings suggest that the peer-delivered screening and brief intervention program was perceived as acceptable to the youth and feasible to implement. Trial registration NCT04998045 Registration date: 10/08/2021.